RESOLUSI KONFLIK HARTA PUSAKA TINGGI DI MINANGKABAU (Studi di Nagari Gantuang Ciri Kabupaten Solok Propinsi Sumatera Barat) - , yuhelna; , Dr. Najib Azca M.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Conflict of high inheritance is a problem that often occurs in Minangkabau. In fact, the district court in West Sumatera issued form letter that contains every conflict related to sako (honor) and pusako (property in object and non-object form as inheritance) which must be resolved through customary procedures. This study aimed to determine conflict resolution of high inheritance based on customary institution and to determine the effectiveness of conflict resolution of high inheritance based on customary institution in Minangkabau. The formulation of problem of this study is how the stages and mechanisms of conflict resolution of high inheritance based on customary institution are and how the effectiveness of conflict resolution of high inheritance based on customary institution in Minangkabau society is. This study used conflict theory of Lewis Coser with functionalism conflict approach. The method used in this study is qualitative approach with strategy research of phenomenology case study about conflict resolution of high inheritance in Nagari Gantuang Ciri. The techniques of data collection are collected by involved observations and deeply open interviews. Key informants consisting of KAN chairman, conflicted individual informants, and members of KAN, and then supporter informants consisting of family members who involved in conflict of high inheritance and the surrounding communities. This study found that the mapping and conflict typology, process of conflict resolution of high inheritance based on customary institution in Nagari Gantuang Ciri are through 3 stages, namely, first within the clan, second in 3 ninik or 4 ninik and third in customary institution of KAN. Other result is conflict resolution of high inheritance based on customary institution in Nagari Gantung Ciri has advantages and disadvantages. The advantages are inexpensive cost (low cost), opportunity of bribing is small, and conflict resolution is solved by discussion system. However, conflict resolution based on customary in Nagari Gantuang Ciri also has a number of disadvantages such as lack of human resources (SDM) of ninik mamak, lack of full supports from government related to reward of ninik mamak efforts and no regulation of the local government that confirming the existence of KAN as an institution that has authority in conflict resolution of high inheritance.